Fatty acid composition of erythrocyte membranes in carries of rs174544 polymorphism of FADS1 gene and rs174583 polymorphism of FADS2 gene from central region of the Russian Federation before and after supplementation of their diet with ω-3 PUFAs - Nataliya Mikhailovna Shilina; Elena Yurievna Sorokina; Mariia Andreevna Makarenko; Vladimir Vladimirovich Bessonov (Human Nutrition & Metabolism, 2024)
Numerous publications have demonstrated that polymorphisms in FADS1 and FADS2 gene cluster influence the levels of long chain polyunsaturated fatty acids (LC PUFAs) synthesized in the body from essential precursors. They can be consumed through the diet as well. These LC PUFAs perform important plastic and regulatory functions in the body. The associations between the polymorphisms of FADS genes and the fatty acid (FA) composition of the body with some inflammatory and chronic diseases were shown. To date, very few studies in the Russian Federation researched the distribution of polymorphic variants in FADS1 and FADS2 genes and no studies examined the effects of these polymorphisms on the level of FAs in tissues.So, the purpose of this paper was to study the frequency of genotypes and alleles of the rs174544 polymorphism of the FADS1 gene and the rs174583 polymorphism of the FADS2 gene and their influence on the FA composition of erythrocyte membranes in residents of the Central region of the Russian Federation (RF). Additionally, the effect of ω-3 PUFAs fortified food products on this composition was examined. Methods: The study included 70 volunteers aged 23–69 years from Moscow region who provided informed consent. They were genotyped for rs174544 polymorphism of FADS1 gene and rs174583 polymorphism of FADS2 gene by real-time PCR. The participants of the study consumed fruit or vegetable smoothies enriched with either vegetable (chia seeds flour) or animal (fish oil flour) sources of ω-3 PUFAs for 1 month. The fatty acid composition of erythrocyte membranes in some of the volunteers was analysed using gas-chromatography before and after fortification of their diet with ω-3 PUFAs. Statistical analysis was performed using SPSS 23. Results: The frequency of genotypes and alleles of polymorphisms studied were similar to those published for the European region. For rs174544, the genotype frequencies were CC (61%), CA (29%), and AA (10%), frequency of allele A was 24%. For rs174583, the genotype frequencies were CC (51%), CT (39%), and TT (10%), frequency of allele T was 29%. Carriers of minor alleles of both polymorphisms studied had significantly higher levels of ω-6 and ω-3 LC PUFAs in erythrocyte membranes compared to those carrying other genotypes. This differs from the results of other studies where carriers of minor alleles as were shown to be slow converters of precursors to LC PUFAs. The reason of the discrepancy was most likely associated with the obesity and dietary preferences of our study participants who carry the minor alleles. Over the period of one-month consumption of food sources providing an additional intake of either 2 g/day ω-3 PUFAs from fish oil or 6.5 g/day of ω-3 PUFAs from chia seed flour markedly reduced the incorporation of ω-6 PUFAs into erythrocyte membranes in carriers of minor alleles. Additionally, there was an increase in the content of saturated palmitic acid in the membranes that noticeably changed the fatty acid composition of erythrocyte membranes. Conclusion: Our results confirm the observation that blood fatty acid composition related to polymorphisms of FADS gene is highly influenced by BMI. The incorporation of ω-6 PUFAs into erythrocyte membranes decreases when the diet is fortified with ω-3 PUFAs. This decrease can help reduce the formation of pro-inflammatory eicosanoids and the risk of various inflammatory and chronic diseases, especially in carriers of minor alleles of the genetic polymorphisms studied.